Gel Chromatographic Examination of Serum of Rats and Hamsters Under Artificial and Natural Hibernation - Shylo, Oleksandr; Lomako, Viktoria; Semenchenko, Oleksandr (Problems of Cryobiology and Cryomedicine, 2021)
In this study, molecular composition of hamster and rat blood was studied by gel permeation chromatography under natural (NH) and artificial hibernation (AH). The control group was represented by 5 fractions of molecules in hamsters and 7 in rats. The areas under peaks of the fractions similar in molecular weight in hamsters and rats were larger in rats. NH was characterized by appearance of new fractions (1,350, 2,350, and 6,350 Da) and an increase in areas under peaks of the control fractions (1,140 and 1,980 Da). Artificial hibernation in rats led to an increase in areas under peaks of 1,140 Da fraction, a decrease in that of 530 Da, and disappearance of 1290 Da, as well as the appearance of new fractions (650, 830, 950, 2350, and 5110 Da). Two hrs of later AH, the areas under peaks of 1,140 and 1,520 Da fractions were greater and that of 530 Da was lesser; 650, 2,350 and 5,110 Da fractions disappeared, 1,290 Da reappeared and new fraction of 4,030 Da appeared. New fractions of 5,820 and 6,530 Da were found 24 hrs later. In hamsters under AH, the areas under peaks of 1,140, 1,600, and 3,330 Da increased; as well as a new peak in 5,280 Da appeared, both in the control rats and those in 24 hrs after AH. Probl Cryobiol Cryomed 2021; 31(3): 191–202